2020
DOI: 10.1097/md.0000000000023045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics, prebiotics and synbiotics for chronic bronchitis or chronic obstructive pulmonary disease

Abstract: Background: Probiotics, prebiotics and synbiotics have been widely used in the treatment of respiratory diseases, but their clinical efficacy for treating chronic bronchitis (CB) or chronic obstructive pulmonary disease (COPD) has not been well studied. Methods: The following electronic databases will be searched for eligible randomized controlled trials: the Cochrane Library, EMBASE, MEDLINE, PubMed, Scopus, the Web of Science, the China National Knowledge Infrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This result is relevant to a study that showed that EEP is potentially enough to treat lung inflammation by reducing the inflammation process and oxidative stress oxidative [24]. In contrast, the efficacy and safety of synbiotics in treating some lung diseases are still questionable [25].…”
Section: Discussionmentioning
confidence: 83%
“…This result is relevant to a study that showed that EEP is potentially enough to treat lung inflammation by reducing the inflammation process and oxidative stress oxidative [24]. In contrast, the efficacy and safety of synbiotics in treating some lung diseases are still questionable [25].…”
Section: Discussionmentioning
confidence: 83%
“…Pei C et al 14 confirmed that comprehensive intervention with probiotics based on conventional drug therapy for COPD can further alleviate patients' clinical symptoms and improve the overall therapeutic effect. Karim A et al 15 also pointed out that adding probiotics to the routine treatment regimen of COPD patients not only improves their walking speed and grip strength, but also has a positive effect on downregulating the expression of C-reactive proteins and reducing the degree of inflammation in the body.…”
Section: Discussionmentioning
confidence: 96%
“…[ 21 ] It has been confirmed that the auxiliary intervention of probiotics based on symptomatic treatment of COPD can improve the muscle function, strength, and body function of COPD patients by stabilizing neuromuscular and regulating intestinal permeability. [ 20 , 21 ] A recent meta-analysis by Pei C et al [ 22 ] confirmed the important role of probiotics in alleviating clinical symptoms, improving lung function, and ensuring good disease outcomes in patients with COPD. Jamarkandi SA et al [ 23 ] also confirmed that there are many risk factors that can cause gut microbiota imbalance and intestinal microecology disorder in the pathogenesis and progression of COPD, resulting in increased secretion and synthesis of endotoxins, but the above problems can be improved by the application of probiotics.…”
Section: Discussionmentioning
confidence: 99%